2023
DOI: 10.3390/buildings13081888
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Design and Operations Management of Metro-Based Underground Logistics Systems: A Thematic Literature Review

Abstract: Sustainable urban development relies on forward-looking infrastructure development. As an emerging infrastructure system that incorporates green technologies, the Metro-based Underground Logistics System (M-ULS) enables sustainable transportation of passengers and freight within cities collaboratively by sharing rail transit network facilities. M-ULS can effectively save non-renewable energy and reduce pollution to the ecological environment, and the comprehensive benefits of the system make an outstanding con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…One form of ULS is metro-based ULS, or M-ULS -also significantly contributed to by Chinese research -that can synergistically combine freight and passenger transport under the same dynamically managed infrastructure network [37]. A recent literature review in M-ULS -purporting to be the first of its kind -found that the system brings wide ranging and comprehensive sustainability benefits to society, from energy savings and more fluid transportation to environmental, economic and social benefits, but also that these benefits scale with the system, meaning as the scale of the network grows, the positive impacts on sustainability also become more pervasive [38].…”
Section: The Future Of Urban Logistics Infrastructurementioning
confidence: 99%
“…One form of ULS is metro-based ULS, or M-ULS -also significantly contributed to by Chinese research -that can synergistically combine freight and passenger transport under the same dynamically managed infrastructure network [37]. A recent literature review in M-ULS -purporting to be the first of its kind -found that the system brings wide ranging and comprehensive sustainability benefits to society, from energy savings and more fluid transportation to environmental, economic and social benefits, but also that these benefits scale with the system, meaning as the scale of the network grows, the positive impacts on sustainability also become more pervasive [38].…”
Section: The Future Of Urban Logistics Infrastructurementioning
confidence: 99%
“…This model facilitated the seamless integration of underground logistics systems with ports, thereby enhancing port operational efficiency and mitigating traffic congestion. However, in addition to cost, the planning of an underground logistics network also needs to consider several other factors, such as robustness, fragility, and resilience [24]. Underground logistics networks face huge sunk costs once they are put into practice.…”
Section: Underground Logistics Networkmentioning
confidence: 99%